Inflated how money and debt built the American dream - Whalen, R. Christopher, 1959- (Wiley, 2011)
"Americans as a whole view themselves as reasonably prudent and sober people when it comes to matters of money, reflecting the puritan roots of the earliest European settlers. Yet as a community, we also seem to believe that we are entitled to a lifestyle that is well-beyond our current income, a tendency that goes back to the earliest days of the United States and particularly to get rich quick experiences ranging from the Gold Rush of the 1840s to the real estate bubble of the early 21st Century. Inflated examines this apparent conflict and makes the argument that such a world view is so ingrained in us that to expect the United States to live in a "deflated" world is simply unrealistic. It skillfully seeks to tell the story of, money inflation and public debt as enduring (and perhaps endearing) features of American life, rather than something we can one day overcome as our policy makers constantly promise. Features interviews with today's top financial industry leaders and insiders. Offer a glimpse into the future of the Federal Reserve and the role it will play in the coming years. Examines what the future may hold for the value of the U.S. dollar and the real incomes of future generations of Americans. The gradual result of the situation we find ourselves in will inevitably lead to inflation, loss of economic opportunity, and a decline in the value of the dollar. This book will show you why, and reveal how we might be able to deal with it."--